Bonecas da moda: um estudo sobre o corpo através da moda e da beleza - Revista Feminina 1915-1936 - Gellacic, Gisele Bischoff (2008)
This research is a revision of articles from the Revista Feminina, a periodical of large circulation in Brazil between the years of 1915 and 1936. Based on the history of the body and of women, an analysis is made of the female figure based on representations of fashion and beauty, and their functions, methods and utilities. The ideal of a slender and well dressed woman is presented to the readers of the Revista as how they should present themselves to fit in with the society of that period. An analysis is made of the means used by the Revista to convince its readers to exert their femininity by presenting this image. The dialogue between modernity, medical/hygiene and urban discourses is intensively used in the articles to justify a beautiful and fashionable appearance